Views of Music Teachers on Psycho-Motor Activities - Soykunt, Neriman; Gorgoretti, Başak (Journal of History Culture and Art Research, 2019)
The current study investigated the practices available to develop psycho-motor skills within the context of 8th grade music courses offered at the secondary school level in the Turkish Republic of North Cyprus (TRNC). The central research question focused on exploring how effectively psycho-motor skills-based activities were conducted in 8th grade music classrooms to meet the goals set by the music curriculum, and included three subquestions: (a) What psycho-motor activities are applied in 8th grade music lessons?, (b) What are music teachers’ views of the psycho-motor activities applied in 8th grade music lessons?, and (c) What difficulties are experienced by music teachers regarding the application of psycho-motor activities in music lessons? The research examined music teachers’ views regarding activities used to develop psycho-motor skills to answer these three subquestions. Qualitative data were collected by conducting semi-structured interviews with 15 music teachers, and data were analyzed through content analysis. Findings revealed that activities for developing psycho-motor skills were designed and used randomly based on music teachers’ preferences and hence were not applied at a required level in an efficient way. Participants indicated that these problems were due to a lack of instructional materials and instruments, lack of appropriate music classrooms, lack of supervision and in-service training, and the negative attitude of both families and students towards music lessons. Based on the findings curriculum revisions and suggestions regarding how to develop psycho-motor skills through musical activities are proposed, and the importance of producing a realistic curriculum is emphasized.